Metaphors and social science - Eric D. Macpherson (Discrete Dynamics in Nature and Society)
The social sciences have a considerable history of attempts to apply models and theories from the physical sciences. All such attempts have failed, primarily because social scientists have commonly not distinguished between applications and possibly useful metaphors.